A Novel Means of Assessing Institutional Adherence to Blood Transfusion Guidelines. (November 2015) - Hicks, Caitlin W.; Frank, Steven M.; Wasey, Jack O.; Efron, Jonathan; Gearhart, Susan; Fang, Sandy; Safar, Bashar; Makary, Martin A.; Wick, Elizabeth C.
Risk-adjusted institutional transfusion rates are not currently available on a national level. A surrogate means of benchmarking transfusion practices to use for internal quality improvement was studied. Blood utilization was prospectively studied among all colorectal surgery patients at the study institution (July 2010-November 2012), and these data were benchmarked with transfusion data from the National Surgical Quality Improvement Program (NSQIP) database by hospital type and size. Using NSQIP, the study institution's colorectal surgery transfusion rate was 16.3% (150/920 cases), which was slightly higher than the 14.3% national mean transfusion rate (12 191/85 507 cases; P = .08). When broken down by hospital type and size, the study hospital had a similar rate of blood transfusion compared with academic hospitals ( P = .35) but a significantly higher rate than community hospitals, regardless of patient volume ( P = .03). Benchmarking blood utilization compared with similar-type hospitals using NSQIP may be a surrogate method to assess adherence to evidence-based transfusion guidelines and identify areas for structured quality improvement initiatives.